(3GSJKeGQGJ GdTQcGJ eJYOOI GdLfSjGJ aj JcfhdhLjG GdWGbI GdeJLOOI (B=s Multinational corporation's investements in renawable energy technology - (3GdSHGYj, eMeO UdGM,s 1973- ((3GdEScfOQjI, eUQ (B:s (3OGQ GdacQ GdLGeYj,s, 2017)
(3ONdJ GdYdGbGJ GdGbJUGOjI GdOhdjI eQMdI eJTGHcI aj YdGbGJgG fJjLI dJYejb eHOC GdGYJeGO GdeJHGOd Pdc GdeHOC GdPj JCUd fJjLI JbGQH GdCShGb hJQGHWgG hCUHMJ GdTQcGJ eJYOOI GdLfSjI ; JXgQ cbhI eDKQI aj GdYdGbGJ GdGbJUGOjI GdOhdjI, hCUHMJ JDKQ HTcd eJRGjO Ydi GdfXGe GdGbJUGOj GdYGdej GdLOjO, eKd JYejb GdYhdeI (B( Globalization) (3aj cGaI GdeSJhjGJ GdEfJGLjI hGdJcfhdhLjI hGdJShjbjI hGdJehjdjI hGdEOGQjI, HGdEVGaI Edi GdJCKjQ Ydi JhLgGJ GdGSJKeGQ GdOhdj hGdJLGQI GdOhdjI, hCfeGW GdJNUU hJbSje GdYed GdOhdj, MJi Cf CMO GdJbGQjQ GdUGOQI YGe (B1992 (3Yf CeGfI GdCee GdeJMOI, CTGQJ Edi Cf GdTQcGJ eJYOOI GdLfSjI CUHMJ GdefXe GdeQcRj ddCfTWI GdGbJUGOjI aj GbJUGO YGdei jJRGjO JcGedG dbO GUHM JMQjQ GdGbJUGO hGdGShGb SeI eejRI ddSjGSI GdGbJUGOjI deYXe Ohd GdYGde ; NGUI HYO GfTGA efXeI GdJLGQI GdYGdejI hGJNPJ GdMcheGJ GdYOjO ef GdSjGSGJ HgOa GdJaYjd GdcaA ddGShGb hJSgjd GdhUhd Gdj GdShb GdOhdjI(B.s
(3KHJ GdeUWdMGJ hGdCNJUGQGJ (B: (3UaMI (B275-280.s
(3HHdjhLQGajI (B: (3UaMI (B261-273.s
Keywords: (3eUGOQ GdWGbI GdHOjdIs -- (3LhGfH GbJUGOjIs; (3GdTQcGJ GdOhdjIs -- (3LhGfH GbJUGOjIs